Pengaruh Transparansi, Akuntabilitas Dan Responsibilitas Pengelolaan Keuangan Terhadap Kinerja Guru SMA Negeri 1 Nita - Alfila, Theresia; Jaeng, Wihelmina M. Y.; Lamawitak , Paulus Libu (Jurnal Projemen UNIPA, 2025)
This research aimed to determine the effect of financial management transparency on the performance of teachers at SMA Negeri 1 Nita, the effect of financial management accountability on teacher performance, the effect of financial management responsibility on teacher performance, and the simultaneous effect of transparency, accountability, and responsibility in financial management on teacher performance at SMA Negeri 1 Nita. This research used a quantitative approach, with field data collected through questionnaires and documentation techniques. The research populations consist of 52 teachers of SMA Negeri 1 Nita. Data ware processed using SPSS analysis. The result showed that transparency, accountability, and responsibility had a significant effect on teacher performance, as well as a simultaneous influence of these factors on teacher performance.